Strategies to improve communication management within virtual project teams - Haron, Nuzul Azam; Law, Teik Hua; Hassim, Salihudin; Eftekhari, Fathollah; Muhammad, Muhammad Tahir; Harun, Aizul Nahar (Universiti Putra Malaysia Press, 2019)
Working in a virtual team presents many challenges. Communication is one of the most important challenges, especially when a virtual team includes members from different countries and background. Virtual project management enables organizations to save on resources such as cost and time. Organizations often struggle with poor communication in their geographically dispersed teams and ineffective communication have been identified as one of the main causes project failure. The aim of this study is to determine the most critical barriers to effective communication in virtual teams. A mixed method of data collection was adopted using semi structured interview with communication and construction experts, and questionnaire approach with construction companies that are G5-G7 rated. Data were analyzed using pareto and exploratory factor analysis for the development of a strategy for enhancement of communication management within virtual teams. The result shows that lack of trust and misunderstanding are the most important barrier to communication within virtual teams. However, managing communication process has been identified to have more impact on the barriers, while planning communication has the least impact. Establishing rule for response and changing focus from individual to group were identified as the two most important factors required in order to sustain trust within virtual teams.